The unsustainable American state - Jacobs, Lawrence R.; King, Desmond S. (Oxford University Press, 2009)
The complexity of the American economy and polity has grown at an explosive rate in our era of globalization. Yet as the 2008 financial crisis revealed, the evolution of the American state has not proceeded apace. The crisis exposed the system's manifold political and economic dysfunctionalities. Featuring a cast of leading scholars working at the intersection of political science and American history, The Unsustainable American State is a historically informed account of the American state's development from the nineteenth century to the present. It focuses in particular on the state-produced inequalities and administrative incoherence that became so apparent in the post-1970s era. Collectively, the book offers an unsettling account of the growth of racial and economic inequality, the ossification of the state, the gradual erosion of democracy, and the problems deriving from imperial overreach. Utilizing the framework of sustainability, a concept that is currently informing some of the best work on governance and development, the contributors show how the USA's current trajectory does not imply an impending collapse, but rather a gradual erosion of capacity and legitimacy. That is a more appropriate theoretical framework, they contend, because for all of its manifest flaws, the American state is durable. That durability, however, does not preclude a long relative decline.